The implementation of reclamation on paddy field as preparation for Sekolah Menengah Kebangsaan Agama Jerlun, Padang Sera Kodiang Kedah Darul Aman / Muhammad Shukur Omar - Omar, Muhammad Shukur (2015)
Earthwork is one of important stage in construction . All the process from the site clearing and the final stage of earthwork must follow the specification from Jabatan Kerja Raya . Any non corfomance product that given by contractor will be noticed by JKR . The site of Sekolah Menengah Kebangsaan Agama Jerlun is the site of former paddy field and it contain of unsuitable soil material . So the contractor must remove all the unsuitable soil material to another dump . The soil imported from the quary also must be approval by JKR . The types and characteristics also must suitable . Before the imported filling transport to our site , the contractor must get the permission from local authority which is Pejabat Tanah Daerah . The approval from Pejabat Tanah Daerah will proceed our back fill work and the imported soil can be transport . All the machineries and lorry must work well so that our work can run smoothly .The safety on site also must be focus. Toolbox meeting which is conduct by site safety supervisor must be attend by all the labour .